Accelerated pavement testing in Costa Rica - Leiva Villacorta, Fabricio (2025)
Accelerated pavement testing equipments such as Heavy Vehicle Simulator (HVS) help evaluate pavement performance in a short period pf time. The objective of this research project is to characterize, improve and introduce new materials and technologies, generate or improve specifications and develop a pavement design guide for Costa Rica. The first experimental test tracks were built at the National Laboratory of Material and Structular Models of University of Costa Rica (LanammeUCR). The results of the first experiment will be used as the standard methodology to apply on future tests.